Standard specification for Free-Cutting Brass Rod, Bar and Shapes for Use in Screw Machines (American Society of Testing Materials, 2005)
This specification establishes the requirements for freecutting brass rod, bar, wire, and shapes of any specified cross section produced from Copper Alloy UNS No. C36000 suitable for high-speed screw machining applications and moderate thread rolling.